O-269 Long-term development of children born from CAPA-IVM and IVF: follow-up of a randomized controlled trial. (30th June 2022) - Vuong, L.N; Nguyen, M.H.N; Nguyen, N.A; Ly, T.T; Tran, V.T.T; Nguyen, N.T; Hoang, H.L.T; Pham, T.D; Smitz, J; Mol, B.W; Norman, R.J; Ho, T.M
Abstract: Study question: Is there any difference in developmental outcomes in children born after capacitation in vitro maturation (CAPA-IVM) compared with conventional in vitro fertilization (cIVF)? Summary answer: Overall development up to 24 months of age was comparable in children born after CAPA-IVM compared with cIVF. What is known already: IVM has been shown to be a feasible alternative to conventional IVF in women with a high antral follicle count (AFC). Data from a randomized clinical trial did not show non-inferiority of CAPA-IVM compared with cIVF with respect to live birth rate, although the findings did approach inferiority for IVM versus IVF when cumulative outcomes were considered (cumulative ongoing pregnancy rates of 44% versus 63%). In addition to live birth rate, childhood development is also a relevant metric to compare between the two approaches to assisted reproductive technology (ART) and there are currently no data on this. Study design, size, duration: This study was a follow-up of babies born to women who participated in a randomized controlled trial comparing CAPA-IVM with cIVF (Vuong LN et al, Hum Reprod 2020;35:2537-2547). Developmental assessments were performed on children over 24 months of follow-up. Participants/materials, setting, methods: Randomized trial participants had an indication for ART and a high AFC (≥24 follicles in both ovaries) were randomized to undergo one cycle of either CAPA-IVM (n = 273) or IVF (n = 273). Of these, 96 women and 118 women, respectively, had live births. Seventy-six women (94 children, 79.2%) and 104 women (137 children, 88.1%), respectively, completed Ages & Stages Third Edition (ASQ-3) Questionnaires, and assessment of Developmental Red Flags at 6, 12 and 24 months of age. Main results and the role of chance: Baseline characteristics of follow-up study participants in the CAPA-IVM and IVF groups were comparable. Overall, there were no significant differences in ASQ-3 scores at 6, 12 and 24 months between children born after CAPA-IVM or IVF. The proportion of children with developmental red flags was low and did not differ between groups. The only significant difference between the CAPA-IVM and IVF groups was for ASQ-3 scores in problem solving and personal-social in twins only at 6 months. These scores were slightly lower in the CAPA-IVM versus IVF group but were still within the normal range and had caught up to the IVF group in the 12- and 24-month assessments. Twenty-eight babies in the IVM group and 26 in the IVF group had an abnormal ASQ-3 on at least one occasion (36% versus 25%, relative risk [RR] 1.6, 95% confidence interval [CI] 0.99–2.5, p = 0.08). All babies with abnormal ASQ-3 were referred to a specialist. Four babies in the IVM and two in the IVF group were confirmed to have abnormal mental and/or motor development (RR 2.9, 95% CI 0.54–15.6, p = 0.23). Children in both groups showed normal and comparable growth with respect to body weight over the first 24 months. Limitations, reasons for caution: This study is an open-label follow-up of participants in a randomized controlled trial, and not all original trial subjects took part in the follow-up. Wider implications of the findings: These data add to the evidence available to physicians when considering different approaches to fertility treatment and justify further surveillance. Trial registration number: NCT04296357